Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1086/117709
|View full text |Cite
|
Sign up to set email alerts
|

Lyman Imaging of High-Redshift Galaxies.III.New Observations of Four QSO Fields

Abstract: We present the results of deep Lyman limit imaging in four new elds as part of a continuing search for galaxies at 3:0 z 3:5. The technique uses a custom broad{band lter set (U n GR) designed to isolate objects having Lyman continuum breaks superposed on otherwise at{spectrum ultraviolet continua. The observations are speci cally aimed at detecting known galaxies producing optically thick QSO metal line absorption systems, but are equally sensitive to more generally distributed objects at the redshifts of inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
272
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(281 citation statements)
references
References 28 publications
8
272
0
Order By: Relevance
“…where light is generated by stars) at high redshifts has seen a tremendous progress in the last years thanks to programs employing the Lyman break technique (cf. Steidel et al 1995Steidel et al , 1996Steidel et al , 1999, and projects like the Hubble Deep Field (HDF, Williams et al 1996). Steidel and collaborators (1996) have shown that on the order of a few percent of the galaxies at faint optical magnitudes (R ∼ 25) are actively star forming galaxies at redshift greater than 3.…”
Section: Star Forming Galaxies At High Redshiftmentioning
confidence: 99%
“…where light is generated by stars) at high redshifts has seen a tremendous progress in the last years thanks to programs employing the Lyman break technique (cf. Steidel et al 1995Steidel et al , 1996Steidel et al , 1999, and projects like the Hubble Deep Field (HDF, Williams et al 1996). Steidel and collaborators (1996) have shown that on the order of a few percent of the galaxies at faint optical magnitudes (R ∼ 25) are actively star forming galaxies at redshift greater than 3.…”
Section: Star Forming Galaxies At High Redshiftmentioning
confidence: 99%
“…The discretization was performed considering the Lyman Break Method [Steidel, Hamilton, 1992;Steidel et al, 1995], based upon broad spectral features that can be easily identified. These include the Lyman Alpha Break and the Lyman Limits.…”
Section: Bzk Atrributes: (B-v)-(v-r) (V-r)-(r-i) (R-i)-(i-z)mentioning
confidence: 99%
“…The original U n GR-based colours of Steidel, Pettini & Hamilton (1995) have more recently been 'tuned' (see Adelberger et al 2004) to select galaxies at mean redshifts z = 3.0 (LBGs), 2.2 (BX galaxies) and 1.7 (BM galaxies), in each case with a redshift dispersion of about 0.3 (see Figure 1).…”
Section: Dwarf Ellipticals At High Redshiftsmentioning
confidence: 99%